Batı klasik müzik etkinliklerinde görgü kuralları: alkışlama kuralı üzerine bir çalışma - Karşıcı, Gülay (My University, 2019)
The data gathered through dozens of activity observations focusing on the clapping rule mentioned in the etiquette of Western classical music activities, participatory observation as a chorist member in polyphonic choirs and the data collected through interviews with fifty people about this music have shaped this article. This qualitative study was carried out to understand how the non-compliance with the rule of applause was perceived by the Western classical music scene, the judgments about the audience who did not abide by the rule, the reactions to the untimely applause and the reasons for the applause. Both the field study methods and techniques, as well as the classical concert etiquette collected by literature review, were listed in a certain order. While I think that many rules of etiquette in these articles should be followed not only in activities but also in social life, I think that some rules such as clapping (applauding) rule are over-valued and will not be observed in the future.
Keywords: Klasik Konser İzleme Adabı, Alkışlama Kuralı